Workplace assessment in crisis? The way forward. (April 2016) - O'Leary, Denis; Al-Taiar, Hasanan; Brown, Nicholas; Bajorek, Tomasz; Ghazirad, Marjan; Shaddel, Farshad
Summary: A recent Royal College of Physicians' study on assessment raises serious questions for workplace assessment. To address these, a system is recommended that bridges the gap from competence to performance and integrates supervised learning events (SLEs) that are formative in purpose with summative assessment of performance by entrustable professional activities (EPAs).